2021
DOI: 10.1186/s13287-021-02366-x
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from induced pluripotent stem cell-derived mesenchymal stem cells accelerates cutaneous wound healing through enhanced angiogenesis

Abstract: Background Mesenchymal stem cells (MSCs) can improve cutaneous wound healing via the secretion of growth factors. However, the therapeutic efficacy of MSCs varies depending upon their source. Induced pluripotent stem cells are emerging as a promising source of MSCs with the potential to overcome several limitations of adult MSCs. This study compared the effectiveness of conditioned medium of MSCs derived from induced pluripotent stem cells (iMSC-CdM) with that derived from umbilical cord MSCs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…The reduced angiogenic ability contributes to impaired wound healing and therefore pro-angiogenic therapy is highly desirable. It was shown that topical application of conditioned medium from induced pluripotent stem cells [39] or hydrogel-mediated delivery of umbilical cord blood-derived MSC [36] accelerates wound healing through enhanced angiogenesis. Our results clearly show that the supplementation of hydrogel with HATMSCs supernatant improves the tube formation process in angiogenic test in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced angiogenic ability contributes to impaired wound healing and therefore pro-angiogenic therapy is highly desirable. It was shown that topical application of conditioned medium from induced pluripotent stem cells [39] or hydrogel-mediated delivery of umbilical cord blood-derived MSC [36] accelerates wound healing through enhanced angiogenesis. Our results clearly show that the supplementation of hydrogel with HATMSCs supernatant improves the tube formation process in angiogenic test in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…hiPSC-MSCs showed better proliferation, survival, immunomodulatory properties, and therapeutic efficacy for myocardial repair than BM-MSC and possessed the capacity to transfer mitochondria to rescue mitochondrial dysfunction [ 6 , 48 ]. In accordance with their findings, our group showed that conditioned medium of hiPSC-MSC (iMSC-CdM) was superior to that derived from umbilical cord MSC in accelerating wound closure [ 45 ]. GMP-grade hiPSC-MSCs have been applied in acute steroid-resistant graft versus host disease (GVHD) in clinical trials [ 49 ].…”
Section: Discussionmentioning
confidence: 53%
“…We also found that Apelin-13 pretreatment greatly enhanced the angiogenic capacity of MSCs, as evidenced by the increased capillary-like tube formation of HUVECs cultured with conditioned medium and enhanced capillary and arteriole density in the ischemic heart tissue. Our previous studies have documented that the ERK signaling pathway is involved in regulating the angiogenic capacity of MSCs [ 25 , 45 ]. In this study, we also observed that inhibition of the ERK signaling pathway with U0126 significantly downregulated the angiogenic capacity of Apelin-13-treated MSCs, indicating that Apelin-13 stimulates the angiogenic capacity of MSCs by activating the ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been well demonstrated that conditioned medium from iPSC‐derived MSCs has multiple impacts in the healing of full‐thickness excisional wounds as compared with umbilical cord‐derived MSCs. Indeed, they stated that this conditioned medium could stimulate HUVEC proliferation, tube formation, and energy metabolism via the ERK pathway 65 . According to the literature, it is clear that there is an outstanding opportunity for utilising iPSCs for skin wound healing applications by promoting angiogenesis.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Indeed, they stated that this conditioned medium could stimulate HUVEC proliferation, tube formation, and energy metabolism via the ERK pathway. 65 According to the literature, it is clear that there is an outstanding opportunity for utilising iPSCs for skin wound healing applications by promoting angiogenesis. .…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%